2021
DOI: 10.1021/jacs.1c02298
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Ligand-Functionalized DNA Nanostructure–Cell Interactions

Abstract: Synthesis of ligand-functionalized nanomaterials with control over size, shape, and ligand orientation facilitates the design of targeted nanomedicines for therapeutic purposes. DNA nanotechnology has emerged as a powerful tool to rationally construct two- and three-dimensional nanostructures, enabling site-specific incorporation of protein ligands with control over stoichiometry and orientation. To efficiently target cell surface receptors, exploration of the parameters that modulate cellular accessibility of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 63 publications
2
39
0
Order By: Relevance
“…[ 137 , 145 ]. Besides answering questions regarding nanotechnology, NA constructs can also answer fundamental biological questions, such as receptors organization [ 162 ], cell interactions [ 163 ] or intracellular processes [ 164 , 165 ]. For example, it was recently shown that compaction and cholesterol tagging of structures could increase specificity towards certain blood cells [ 166 ], or that mechanical properties could promote tumour accumulation [ 167 ].…”
Section: Emerging Rna-based Technologiesmentioning
confidence: 99%
“…[ 137 , 145 ]. Besides answering questions regarding nanotechnology, NA constructs can also answer fundamental biological questions, such as receptors organization [ 162 ], cell interactions [ 163 ] or intracellular processes [ 164 , 165 ]. For example, it was recently shown that compaction and cholesterol tagging of structures could increase specificity towards certain blood cells [ 166 ], or that mechanical properties could promote tumour accumulation [ 167 ].…”
Section: Emerging Rna-based Technologiesmentioning
confidence: 99%
“…As various antibodies represent distinct dimensions, their biological activity involving binding affinity also gets influenced [ 31 ]. Cremers et al [ 32 ] have utilized antibody surface grafted DNA nanostructures to demonstrate that although the inherent affinity of targeting antibody remains unaltered, the number of antibody–receptor interactions remains lower than soluble antibodies governed by nanoconstruct’s size and orientation. Based on these observations, the authors concluded that larger DNA nanostructures may cause steric hindrance and are the primary cause of reduced receptor binding potential.…”
Section: Design and Development Of Multivalent Targeted Nanosystemsmentioning
confidence: 99%
“…295 However, compared with the extensive research on the interaction between DNA ligand patterns and cells, research on the effect of the ligand pattern on the DNA structure on virus recognition is still rare at present. 296,297 Therefore, further research is required in this field.…”
Section: Interaction Between Dendrimers and Virusesmentioning
confidence: 99%